Mortality analysed by propensity score matching: an application to national neonatal audit - Longford, Nicholas T. (Brazilian Journal of Biometrics, 2023)
Mortality, a key outcome variable in many population studies and studies of healthcare and its interventions, is commonly analysed by regression of the survival status on a set of relevant background variables. We describe an alternative based on the potential outcomes framework, in which we ask how a particular group of subjects, or a population, whose outcomes were realised in one condition, would have fared had they been treated or cared for in different circumstances. The method is applied to neonatal mortality in the operational delivery networks in England and Wales. The performance of a network is assessed by the difference of the mortality rates of the network and of a matched set of babies drawn from the entire domain of the study. The outlier status of a network is established by a decision-theoretical approach.